Overview of the participation of community health workers in primary health care in 6 Latin American countries and a proposal for their integration into the health system: a qualitative study (2024)
Background: According to some health programmes, implementing primary health care through community health workers (CHWs) facilitates the connection between community and health services in Latin America. However, these are isolated processes that face different obstacles and would benefit from an overview of the corresponding health policies and programmes. Objective: To provide an overview of CHW participation in 6 Latin American countries. Methods: This exploratory qualitative study was based on 3 sources of information: a literature review, a review of public health policy documents, and interviews with experts who have led CHW programmes in 6 Latin American countries. Results: The role of CHWs in Latin America and some advances in public health policies in the region were evidenced. However, limitations arising from variable implementation of the WHO guidelines on health programmes with CHWs were also apparent. Conclusions: CHWs contribute to the primary healthcare processes in the 6 Latin American countries studied in versatile and comprehensive ways. However, they constitute an underutilized human resource because they must provide various services that are not always relevant in different work contexts. Therefore, we propose a classification of the CHW profile, using the level of access to healthcare services of the population they serve as the main differentiator. This way, CHWs will not have to provide a wide range of services but only those most relevant to the specific needs of each community.